Musculoskeletal disorders analyzing of air cleaner assembly operators using Nordic body map in excavator manufacturer in Indonesia - Galih Prakoso; Hardianto Iridiastadi; Euis Nina Saparina (Operations Excellence: Journal of Applied Industrial Engineering, 2019)
Musculoskeletal disorders often occur in non-ergonomic work postures. In this study an assessment of operator disorders was carried out on the installation of air cleaner components in a heavy equipment manufacturer. The purpose of this study was to determine the extent to which operator disorders and which body parts needed to improve work posture. The assessment method uses a standard Nordic Body Map questionnaire that is often used to assess musculoskeletal disorders. From the results of the assessment, the main disorders were in the right and left elbow body parts at 93%. Second, 87% of the body's right knee and left knee, third, right and left forearm, 80% right and left wrist, fourth on the second upper arm and 73% on the palm. The fifth is on the right shoulder, back and calf 60%. Therefore in these body parts, it is necessary to improve work posture to reduce the risk of musculoskeletal injury. An installation tool is needed for the process to make it easier for operators to work.